Uncommon presentation of a chronic recurrent symptomatic encapsulated calcified postoperative paraspinal lumbar hematoma: A case report - Timothy Edwards; Shaan Sadhwani; Brendan Sweeney; Antonio Almeda-Lopez; Walter C Peppelman; William J Beutler (SAGE Open Medical Case Reports)
Paraspinal hematomas are common complications following spine surgery. In general, these hematomas are asymptomatic and resolve without issue. Unfortunately, there is a paucity of literature that describes the recurrence of these hematomas in a chronic setting. This case report describes a patient with a chronic recurrent calcified paraspinal hematoma that first developed over 4 years and then reoccurred 11 years later at the same site. The case features a 53-year-old female presented with severe lumbar back pain and right lower extremity radiculopathy in which she underwent a lumbar decompression posterior spinal fusion from L3 to L5 in 2008. Postoperatively, she developed a lumbar paraspinal hematoma which was treated with aspiration followed by conservative management. Four years later, the patient had a large paraspinal mass removed from a similar location in an outside medical facility. The procedure required the assistance of plastic surgery for flap closure and a pathologic review of the mass revealed a calcified hematoma. Ten years later, the patient sought treatment from her index surgeon for a recurrence of the lumbar mass with new onset radicular symptoms. Magnetic resonance imaging of the lumbar spine confirmed the presence of a large paraspinal mass. The patient proceeded with the removal of hardware, revision of laminectomy, revision of posterior instrumentation from L2 to L5, and removal of the lumbar mass. The pathology report classified the mass as a chronic calcified hematoma. The patient remains symptom-free for 1 year following the revision procedure. This case demonstrates an extremely rare presentation, ill-described in the existing literature, of a recurrent symptomatic calcified lumbar paraspinal hematoma requiring repeat operative intervention.